Plant biotechnology - its role in improvement of spices - BABU, K NIRMAL; MINOO, D; GEETHA, S P; SAMSUDEEN, K; REMA, J; RAVINDRAN, P N; PETER, K V (The Indian Journal of Agricultural Sciences, 2013)
Spices have played a significant role in the history of civilization. Crop improvement in spices is difficult and time consuming due to their long pre-bearing age and other crop specific problems. Biotechnology offers novel avenues for crop improvement of spices. This paper reviews the present status of biotechnology of spices with emphasis on the work done in India on micropropagation and rapid clonal multiplication of high-yielding elite genotypes to generate good quality planting material, exploiting somaclonal variation and genetic engineering techniques for crop improvement, invitro selection for resistance to biotic and abiotic stresses; in-vitro conservation for safe exchange of germplasm and production of flavour and volatile constituents in culture.